C/O Kerma coefficient ratio for 96 MeV neutrons deduced from microscopic measurements - Göttsche M. (2017)
Double-differential cross sections for neutron-induced light-ion production at 96 MeV have been measured for a variety of nuclei at The Svedberg Laboratory. Using the measured cross-section data, we deduce the Kerma coefficient from carbon and oxygen for p, d, t, 3 He and α particles. In order to get the total Kerma for C and O, we add GNASH calculation values where experimental data are not available and obtain a Kerma coefficient of 7.85 ± 0.63 fGy m 2 for carbon and 7.09 ± 0.57 fGy m 2 for oxygen. The C/O Kerma coefficient ratio then becomes 1.11 ± 0.11. In addition we determine the Kerma ratio between ICRU muscle and A-150, again adding calculations with the GNASH code where no experimental data are available, and obtain a value of 0.98 ± 0.05. While the Kerma coefficients for carbon and oxygen do not agree with the prediction in ICRU Report 63, the ratio values are in good agreement with existing predictions. © 2010 Published by Elsevier Ltd. All rights reserved.